Savings Rates in Turkey: The Prospects For A Sustainable Growth - Yıldırım Mızrak, Nihal; Dastan, Muhammet (International Journal of Economics and Financial Issues, 2018)
The main objective of this study is to reveal the development process of Turkey’s savings rates and investigate the causal relationship between domestic savings and sustainable economic growth by employing Hatemi-J (2012) asymmetric causality test under the time series analysis for the period of 1980-2016. Results of the study indicate that the problem of the inadequate level of domestic savings has not been solved yet in Turkey. It is seen that domestic savings in Turkey have remarkably declined mainly from the 1990s and remain considerably low level at 14 percent over the past few years. It is also seen that Turkey’s domestic savings remain considerably below that of the world average and most of the different income group countries. Besides, Hatemi-J (2012) asymmetric causality test results indicate that there is an existence of causality running from positive shocks on real GDP (RGDP) to positive shocks on gross domestic savings (GDS) at 1% significance level while positive shocks on GDS cause positive shocks on RGDP at 5% significance level. This study, however, could not find evidence of any causal relationship between negative shocks on GDS (RGDP) and negative shocks on RGDP (GDS) at an appropriate significance level. Keywords: Sustainable Growth, Domestic Savings, Hatemi-J Asymmetric Causality Test. JEL Classifications: C22, E21, O40